ANALISIS KETENAGA KERJAAN PADA BEBERAPA PABRIK KAYU LAPIS DI SUMATERA DAN KALIMANTAN - Akub J Abdurachman; Sylviani Sylviani (Jurnal Penelitian Hasil Hutan, 1990)
An analysis of man power has been conducted in several plywood  mills in Sumatera  and Kalimantan in year 1987, and the result presented  in this paper.  The result shows  that  the average employment  is 993 men per mill.Based  on  mill  capasity  and  log input,  the average level  of  labour  absorption  is 11.33 men/1000 cum  designed  capasity, and 10.66 men/1000  cum  log input.  The  latter  figure is  more or less similar to  that  of  the developed  country  in which  the  average  level  of  labour absorption  is.11.33 men/1000  cum.  However  labour  absorption in each  mill  it is not proportional to both capasity  and  material  utilization  (logs). Organization  structure  of mills surveyed  have a long span of control  so it is recommended to be simplified.